2017
DOI: 10.17261/pressacademia.2017.477
|View full text |Cite
|
Sign up to set email alerts
|

Types of information technology capability and their impacts on competitiveness

Abstract: Purpose-This paper aims to examine the impacts of IT Capability and its four sub-dimensions on the firm competitiveness at the logistics sector. IT capabilities have four sub-dimensions as IT infrastructure, IT business experience, IT relationship resources and IT human resources. IT infrastructure capability refers to the combinate hardware, software, network resources and services. IT business experience, is an ability to unify IT strategy and business strategy. IT relationship resource, is a capability to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…The IT capability literature recognizes that competence in mobilizing and deploying IT-based resources is a source of competitive advantage and differentiates firm performance (Bataineh et al, 2015). The IT capability of a company encompasses its technological infrastructure, the human resources with technical and managerial IT skills, and intangible IT-enabled assets like knowledge resources, customer focus, and synergistic elements (Bakan & Sekkeli, 2017).…”
Section: Information Technology Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The IT capability literature recognizes that competence in mobilizing and deploying IT-based resources is a source of competitive advantage and differentiates firm performance (Bataineh et al, 2015). The IT capability of a company encompasses its technological infrastructure, the human resources with technical and managerial IT skills, and intangible IT-enabled assets like knowledge resources, customer focus, and synergistic elements (Bakan & Sekkeli, 2017).…”
Section: Information Technology Capabilitiesmentioning
confidence: 99%
“…A firm's evolution in technology signifies an ongoing process of generating and absorbing technologies that enable the competitive production and provision of valuable products to the market. According to Bakan and Sekkeli (2017), the positive effects of technological capability on firm performance highlight its potential to influence intermediary factors like a firm's learning. Research has demonstrated that technological capability enhances a firm's learning capacity, organizational efficiency, manufacturing proficiency, and resource allocation competence (Panda & Rath, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The IT capability literature recognizes that competence in mobilizing and deploying IT-based resources is a source of competitive advantage and differentiates firm performance (Bataineh et al, 2015). The IT capability of a company encompasses its technological infrastructure, the human resources with technical and managerial IT skills, and intangible IT-enabled assets like knowledge resources, customer focus, and synergistic elements (Mugwe, 2023;Bakan & Sekkeli, 2017). Businesses can enhance their operational performance by effectively utilizing their IT capability to boost earnings, minimize expenses, or achieve both objectives (Adamides & Karacapilidis, 2020).…”
Section: Information Technology Capabilitiesmentioning
confidence: 99%
“…A firm's evolution in technology signifies an ongoing process of generating and absorbing technologies that enable the competitive production and provision of valuable products to the market. According to Bakan and Sekkeli (2017), the positive effects of technological capability on firm performance highlight its potential to influence intermediary factors like a firm's learning.…”
Section: Introductionmentioning
confidence: 99%
“…In short, IT has become the critical resource and capability for firms to achieve competitiveness (Bakan and Sekkeli, 2017). In particular, based on the well-established Grant's (1991) resource classification, three major types of IT resources have been consistently recognized, including a firm's IT human capital, infrastructure and relational resources (Bhatt and Grover, 2005;Sambamurthy et al, 2003).…”
Section: Hypothesis Development: It It Capabilities and Competitivenessmentioning
confidence: 99%